Targeting α7 nicotinic acetylcholine receptors for chronic pain - Zhou, Ya-Qun; Liu, Dai-Qiang; Liu, Cheng; Xu, Ai-Jun; Tian, Yu-Ke; Mei, Wei; Tian, Xue-Bi (Frontiers in Molecular Neuroscience, 2022)
Despite rapid advances in the field of chronic pain, it remains extremely challenging in the clinic. Pain treatment strategies have not improved for decades as opioids remain to be the main prescribed drugs for chronic pain management. However, long-term use of opioids often leads to detrimental side effects. Therefore, uncovering the mechanisms underlying the development and maintenance of chronic pain may aid the discovery of novel therapeutics to benefit patients with chronic pain. Substantial evidence indicates downregulation of α7 nicotinic acetylcholine receptor (α7 nAChR) in the sciatic nerve, dorsal root ganglia, and spinal cord dorsal horn in rodent models of chronic pain. Moreover, our recent study and results from other laboratories demonstrate that potentiation of α7 nAChR attenuates pain behaviors in various murine models of chronic pain. In this review, we summarized and discussed the preclinical evidence demonstrating the therapeutic potential of α7 nAChR agonists and allosteric modulators in chronic pain. This evidence indicates that potentiation of α7 nAChR is beneficial in chronic pain mostly by alleviating neuroinflammation. Overall, α7 nAChR-based therapy for chronic pain is an area with great promise, but more research regarding its detailed mechanisms is warranted.